FAKTOR-FAKTOR YANG MEMPENGARUHI SENJANGAN ANGGARAN (Studi Empiris Pada OPD Provinsi Jambi) - Ulfah Rosendi Afrilliani; Emrinaldi Nur DP; Julita Julita (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2019)
This study aims to determine the effect of budgetary participation, informationasymmetry, budget emphasis, task complexity, and organizational commitment, clarity ofbudget targets, organizational culture and individual capacity for budgetary slack inRegional Device Organization (RDO), Jambi Province. To collect the data, purpossivesampling technique was applied. The population of this study was all Regional DeviceOrganizations (RDO) in Jambi Province with the total sample of 65 official employeesand OPD agencies in Jambi Province. To analyse the data, Partial Least Square (PLS)was used. Based on the results of the data analysis, it shows that budgetary participation,budget emphasis, organizational commitment, clarity of budget targets andorganizational culture influence budgetary slack. However, asymmetry information, taskcomplexity and individual capacity have no effect on budgetary slack.Keywords: budgetary participation, information asymmetry, budget emphasis, taskcomplexity, and organizational commitment, clarity of budget targets,organizational culture and individual capacity for budgetary slack.